(untitled) (Research, Society and Development, 2022)
The objective of this study was to report the experiences lived in the implementation of educational practices in paternal pregnancy, to describe the planned and implemented actions and to present the difficulties and facilities. This is a descriptive study with a qualitative approach that used theoretical-methodological research assumptions in the form of a report of experience lived in the implementation of educational practices in paternal pregnancy in a Basic Health Unit (BHU). A script was prepared to organize all the actions step-by-step, resulting in three moments. The themes were chosen based on the main issues that encompass the puerperal pregnancy process. In addition to the guidelines, it was also used to carry out a quick test, update the vaccination schedule and encourage the male public to attend health services. We believe that the experience provided an opportunity for reflection and allowed the development of more sensitive perspectives on the peculiarities of male health. It is suggested that a specific discipline covering human health can be inserted in the academic context, stimulating the search and guarantee of assistance to this public during the generalist training of the professional nurse.